Peran Tenaga Kerja Perempuan dalam Meningkatkan Kesejahteraan Keluarga Perspektif Islam - Mas'ut, Mas'ut; Moza Ikthiar, Shaney (Institut Agama Islam YPBWI Surabaya, 2025)
Abstract: This research was conducted to find out how big a role female workers play in improving welfare, especially those at the Shuttlecock company. This research uses qualitative research. In obtaining data, the researcher took primary data obtained through a direct observation process at the Shuttlecock company. Apart from that, the researcher also conducted interviews with company managers and employees of the Shuttlecock company. The results of this research show that female workers At the Shuttlecock company it plays a very important role in improving the welfare of its family, this role is demonstrated by the Shuttlecock company by giving women full labor rights without any differentiation from other groups of employees. At the Shuttlecock company, female workers have the opportunity to work in a supportive environment. They also receive decent wages on a par with men, and have the right to leave and rest breaks in accordance with labor regulations. In this way, the income of female workers is able to meet their daily needs.